(untitled) (Semiárida, 2020)
This work took place in three different grasslands in the Province of La Pampa. The first, located in LAS MERCEDES farm, departament of TOAY, with predominane of Digitaria californica. This warm season species reached 14,4% of crude protein (CP) at the beginning of growing season. LA BAYA VIEJA farm was the second place under study, with predominance of winter season species such as Poa ligularis, Piptochaetium napostaense on which 8,5% and 12,4% of CP were obtained respectively in the grow out after cutting. The third place was LOS GUADALES farm, depatament of CALEU CALEU with predominance, of Pappophorum caespitosum during summer and Medicago minima and Erodium cicutarium in winter, wich resulted 9,8%, 24,8% and 23,8% of CP respectively at the beginning of growing season.